2022
DOI: 10.3390/antiox11020273
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Artemisinin on the Redox System of NADPH/FNR/Ferredoxin from Malaria Parasites

Abstract: FNR and ferredoxin constitute a redox cascade, which provides reducing power in the plastid of malaria parasites. Recently, mutation of ferredoxin (D97Y) was reported to be strongly related to the parasite’s resistance to the front-line antimalarial drug artemisinin. In order to gain insight into the mechanism for the resistance, we studied the effect of dihydroartemisinin (DHA), the active compound of artemisinin, on the redox cascade of NADPH/FNR/ferredoxin in in vitro reconstituted systems. DHA partially in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Based on the similarity with prokaryotic and plant MEP pathways, other enzymes of the MEP pathway were also mapped and studied as a target for various inhibitors ( Wang et al., 2010 ; Saggu et al., 2016 ). This pathway provides multiple opportunities to develop a valuable combination therapy that could be either the various enzymes of this pathway or the redox environment created for the functioning of this pathway ( Saggu et al., 2016 ; Kimata-Ariga and Morihisa, 2022 ).…”
Section: Apicoplast and Mep Pathway Enzymes As Drug Targetsmentioning
confidence: 99%
“…Based on the similarity with prokaryotic and plant MEP pathways, other enzymes of the MEP pathway were also mapped and studied as a target for various inhibitors ( Wang et al., 2010 ; Saggu et al., 2016 ). This pathway provides multiple opportunities to develop a valuable combination therapy that could be either the various enzymes of this pathway or the redox environment created for the functioning of this pathway ( Saggu et al., 2016 ; Kimata-Ariga and Morihisa, 2022 ).…”
Section: Apicoplast and Mep Pathway Enzymes As Drug Targetsmentioning
confidence: 99%
“…However, the role of the apicoplast in ART tolerance is generating significant interest. Genetic mutations associated with ART tolerance include fd ( 32 , 73 75 ) and arps10 ( 32 ), which are localized to the apicoplast, and ATG18, which, although it is not localized to the apicoplast, is associated with apicoplast biogenesis ( 76 ), suggestive of an integral role of the apicoplast in ART tolerance. In comparison, fd mutations (D193Y) inserted and removed from K13 mutant and WT strains by Stokes and colleagues ( 77 ) using gene insertion techniques exhibited no apparent effect on parasite survival.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic and proteomic data analysis of A. fumigatus indicated that an oxidative phosphorylation pathway, as well as an ergosterol synthesis pathway, is consequently misregulated upon exposure to artemisinin [ 64 ], suggesting again that oxidative stress is produced during treatment by artemisinin. Interestingly, a stabilizing mutation in the ferredoxin, known to be involved in the oxidative stress response, confers resistance to parasites treated with artemisinin, in accordance with a protective role of ferredoxin against artemisinin [ 66 ].…”
Section: Targeting the Thioredoxin Reductase Trxrmentioning
confidence: 99%